Cryoneurolysis for Digital Neuralgia in Professional Baseball Players: A Case Series. (4th January 2022) - Shaffer, Johnathon Patrick; Williams, Vernon B.; Shin, Steven
Abstract : Objective: We describe a non-surgical approach to refractory digital neuralgia using cryoneurolysis in a series of 3 professional baseball players. Background: Thumb injuries are common in baseball players and can sometimes be challenging to effectively manage. Depending on the injury, current treatments include anti-inflammatories, immobilization, physical therapy, corticosteroid injections, and/or surgery. A subset of patients, however, fail nonoperative management yet do not have a clear indication for surgery. Cryoneurolysis or cyroanalgesia is an FDA-approved form of neuromodulation, which has been used safely and effectively on a variety of peripheral nerves. The mechanism of action involves percutaneous introduction of a small probe under local anesthetic to nerve tissue using ultrasound guidance. The probe is then cooled to −88°C using nitrous oxide, which results in secondary Wallerian degeneration. Axonal and myelin regeneration occurs completely in 3–6 months. Design/Methods: Visualization of the superficial radial sensory and ulnar digital nerve were obtained under ultrasound. The skin was prepared in sterile fashion. A 22-gauge 1-½ inch needle was then advanced with ultrasound guidance, and local anesthetic was applied. Both treatment sites were marked with skin marker. Cryoneurolysis was employed using a 5 mm tip. 60-second treatment cycles were performed at each site. Each of the cycles resulted in a 5 × 7 mm lesion visible as hypoechoic signal. Results: All 3 players endorsed significant and prolonged relief and were able to return to an elite level of play. Conclusions: This manuscript is subject to all of the limitations of a case series, and larger rigorous studies are needed to illuminate causal inferences. Novel, complex technologies may also be more susceptible to placebo effect. Nonetheless, we are able to report marked efficacy and safety from cryoneurolysis of the ulnar digital nerve and the superficial radial sensory nerve in a small group of elite baseball players with refractory digital neuralgia.